Epoché as an opening to the transcendental field of experience in HusserL (Phenomenology, Humanities and Sciences, 2023)
This article deals with the second Cartesian meditation of Edmund Husserl, the conference: "Cartesian meditations. An introduction to phenomenology". In this meditation he establishes the foundation of a new idea of knowledge, which has as its central point the concept of the transcendental ego (consciousness). To reach this field of knowledge, Husserl is inspired by Descartes and establishes a method to open the way to transcendental knowledge. This method is called phenomenological epoché. Having attained the domain of transcendental self-experience, that is, of the pure ego, it is a matter of making the critique of transcendental knowledge and exploring that knowledge in general. What are the components of transcendental consciousness life? What are the relationships between intentional experiences?  How to reach this level of pure knowledge so far from the natural and psychological attitude of the world? These are the themes of this meditation.
Keywords: epoché; Transcendental Experience; Consciouness; Intencionalidade